2016
DOI: 10.1371/journal.pone.0147801
|View full text |Cite
|
Sign up to set email alerts
|

A Unidirectional Cell Switching Gate by Engineering Grating Length and Bending Angle

Abstract: On a microgrooved substrate, cells migrate along the pattern, and at random positions, reverse their directions. Here, we demonstrate that these reversals can be controlled by introducing discontinuities to the pattern. On “V-shaped grating patterns”, mouse osteogenic progenitor MC3T3-E1 cells reversed predominately at the bends and the ends. The patterns were engineered in a way that the combined effects of angle- and length-dependence could be examined in addition to their individual effects. Results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…During cell migration, topographical guidance-induced direction changes could be observed, including a 180°direction reversal. 42,47 Multiple factors have been reported to affect cell migration direction; however, the actual mechanism remains unclear. In this study, the dynamic changes in cell traction force during directional reversals were analyzed.…”
Section: Characteristics Of Traction Force During Reversed Cell Migramentioning
confidence: 99%
“…During cell migration, topographical guidance-induced direction changes could be observed, including a 180°direction reversal. 42,47 Multiple factors have been reported to affect cell migration direction; however, the actual mechanism remains unclear. In this study, the dynamic changes in cell traction force during directional reversals were analyzed.…”
Section: Characteristics Of Traction Force During Reversed Cell Migramentioning
confidence: 99%
“…The remaining positive photoresist was removed in acetone for 10 min. The Si stamp was coated with trichloro(1H, 1H, 2H, 2H-perfluorooctyl) silane (FOTS) (Sigma-Aldrich, 97%), which acted as an anti-sticking layer [32] (Fig 1C). A 60 μm thick 10:1 (weight ratio, w/w prepolymer to curing agent) PDMS (Sylgard 184, Dow Corning) was spin-coated at 1000 rpm for 60 s on the Si stamp and reversely imprinted onto another Si substrate at 130°C and pressure of 40 bar for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…It could be due to the bent gratings had less intersections with trench sidewalls compared to straight gratings that were perpendicular to trenches below. It had been shown that bent gratings had the effect of reversing cell migration direction [16,30]. When segment length of the bent grating became shorter, more cells migrated in the reversed direction so less cells could move towards…”
Section: Plos Onementioning
confidence: 99%
“…Migration of cells in circulating system has been considered as the key in understanding cancer metastasis and circulating tumor cells [9][10][11][12]. Migration behaviors of cancer cells in two-dimensional system in vitro have been studied including cell migration on micropatterns, under confinement, and cell separation [13][14][15][16][17]. However, there is still limited understanding of cancer cell invasion because the microenvironments used for the studies were quite different from the highly complicated extracellular matrix (ECM) in vivo.…”
Section: Introductionmentioning
confidence: 99%